(untitled) (Lundiana: International Journal of Biodiversity, 2003)
This study was performed along the dam of the Parque Ecológico de Dois Irmãos, at the city of Recife, Pernambuco state, Brazil. Populations of Porphyrula martinica, Gallinula chloropus and Jacana jacana were censused from January 1993 to August 1994. The aim of this census was ascertain the population peaks and the reproduction periods and to assess information about nests, eggs and plumage of these species. Reproduction of P. martinica was recorded from November 1993 to April 1994; for G. chloropus this time was just January 1994; and for J. jacana, from February to July 1993 and 1994. It was also recorded observations about nest building, their structure and material, and information about eggs and nestling from the studied species.